Classification of water forms in lignite and analysis of energy consumption on the drying processes by microwave and fixed bed. (1st October 2019) - Liao, Junjie; Mo, Qiong; Li, Chao; Han, Yanna; Chang, Liping; Bao, Weiren
Abstract: The water contained in lignite generally exists in various forms and the energy required to remove them from coal is also different. Thus, two different rank lignites with different water contents from Yunnan and Inner Mongolia provinces in China were selected for analyses of water forms and dewatering energy consumption. The forms of water contained in these two lignites were classified using differential scanning calorimetry (DSC). The results show that the water in the lignite mainly contains freezable water and non-freezable water, and further the freezable water can be divided into free water and freezable bound water. The water above 40% moisture content of dry coal weight in coal sample is free water; that between 27% and 40% of dry coal weight is freezable bound water; and that less than 27% of dry coal weight is non-freezable water, which is nearly independent of coal rank. Then, the microwave drying and the fixed bed drying devices were employed to dry these two lignites, and the dewatering energy consumption during drying processes were measured and calculated to compare the change of energy consumption for removing different types of water. The results show that 500–600 W microwave field is suitable for drying lignite because the water is difficult to be completely removed under 450 W and slight pyrolysis is prone to occur for lignite when the microwave power is higher than 700 W. The dewatering energy consumption of total moisture in microwave field under 500–600 W is 8.6–15.3 kJ/g H2 O, and those of freezable water and non-freezable water are 8.7–12.5 kJ/g H2 O and 8.5–21.8 kJ/g H2 O respectively. In addition, the dewatering energy consumption of 50 g lignite in fixed bed drying at 120–160 °C is 1.3–3.6 kJ/g H2 O. In order to take advantages of microwave and fixed bed, these two methods are coupled to dry lignite for reducing energy consumption and improving drying efficiency. For the best compromise between drying energy and drying time, it is recommended to use 600 W power microwave field to remove free water in lignite, and then to use the fixed bed to remove the remaining water at 160 °C. The water re-adsorption amount of the upgraded coal is about 1/3 lower than that of raw coal.